Combined Strategy of Endothelial Cells Coating, Sertoli Cells Coculture and Infusion Improves Vascularization and Rejection Protection of Islet Graft - Li, Yang (Public Library of Science, 2013)
Improving islet graft revascularization and inhibiting rejection become crucial tasks for prolonging islet graft survival. Endothelial cells (ECs) are the basis of islet vascularization and Sertoli cells (SCs) have the talent to provide nutritional support and exert immunosuppressive effects. We construct a combined strategy of ECs coating in the presence of nutritious and immune factors supplied by SCs in a co-culture system to investigate the effect of vascularization and rejection inhibition for islet graft. In vivo, the combined strategy improved the survival and vascularization as well as inhibited lymphocytes and inflammatory cytokines. In vitro, we found the combinatorial strategy improved the function of islets and the effect of ECs-coating on islets. Combined strategy treated islets revealed higher levels of anti-apoptotic signal molecules (Bcl-2 and HSP-32), survival and function related molecules (PDX-1, Ki-67, ERK1/2 and Akt ) and demonstrated increased vascular endothelial growth factor receptor 2 (KDR) and angiogenesis signal molecules (FAk and PLC-γ). SCs effectively inhibited the activation of lymphocyte stimulated by islets and ECs. Predominantly immunosuppressive cytokines could be detected in culture supernatants of the SCs coculture group. These results suggest that ECs-coating and Sertoli cells co-culture or infusion synergistically enhance islet survival and function after transplantation.